A Diagnostic Analysis of Junior High School Studentsâ€™ Difficulties in Solving TIMSS Model Mathematics Test - Munaji Munaji; Al Jupri (EduMa: Mathematics education learning and teaching, 2022)
This research aims to diagnose students' difficulties in solving the TIMSS model mathematics test. This research used quantitative descriptive research method. The subjects of study is eighth-grade students of junior high school in Cirebon, Indonesia. Data collection was carried out through a simple random sampling technique including 676 students of junior high school from 13 public and private schools. The research instrument is the TIMSS modelmathematics test in the form of multiple-choice and short answers as many as 35 items which are translated into Indonesian. Data analysis was using cognitive diagnostic modeling (CDM) in R programe. The research result showen: 1) In the knowing Domian have been dificulties to understand: commutative properties ofÂ  on natural numbers, estimating the result of the nearest decimal number, identify the appropriate table with the information on the pictogram graph and read the values of the two line charts; 2) in the applaying Domian have been dificulties in: choose and combine information from two different sources to solve problems with multiple steps and in the number series, in find solutions in linear equations of two variables, compiling and using solutions of linear equations to solve problems, and calculating the side lengths of triangles based on linear equations, symmetry properties of reflection and using information from tables to draw a bar chart and compare two possible events; (3) In reasoning domain have been dificulties in to find number patterns and to use the Pythagorean theorem to find the perimeter of a quadrilateral or triangle